Solubility profile of imatinib in pure and mixed solvents and calculation of thermodynamic properties. (May 2020) - Yang, Zehui; Shao, Danfeng; Zhou, Guoquan
Graphical abstract: Highlights: Study the solubility of imatinib in pure and mixed solvents. Solute-solvent interactions and co-solvency phenomenon were analyzed. Two thermodynamic models were used to evaluate the solubility profile. Some thermodynamic properties of dissolution process were calculated. Abstract: The pharmaceutical salt of imatinib prepared with low purity did not meet the pharmaceutically acceptable quality. The objective of this work is to research the shape of the solubility profile of imatinib in pure and mixed solvents at T  = 273.15–313.15 K. At a given temperatures (from 273.15 K to 313.15 K), the largest the solubility is in toluene (2.205 × 10 −3 at 313.15 K) and the lowest is in acetonitrile (9.739 × 10 −5 at 313.15 K), it decrease based on the following order in different solvents: toluene >  n -propanol > acetone > ethyl acetate > acetonitrile. In system of (acetone +  n -propanol), the solubility of imatinib gave an increase trend until w  = 0.2 firstly, and then decreased with the increasing mass fraction of acetone. Regarding for the system of (ethyl acetate +  n -propanol), it reached to the maximum (1.902 × 10 −3 at 313.15 K) at w  = 0.4. Two thermodynamic models including modified Apelblat equation and Jouyban-Acree model were used to correlate. The maximum values of RAD calculated by modified Apelblat equation are all less than 1.66 × 10 −2, and it is no more than 2.28 × 10 −2 observed in Jouyban-Acree model for mixed solvents. Meanwhile, the positive values of apparent dissolution enthalpy ( Δ H sol o ) and apparent dissolution entropy ( Δ S sol o ) indicate that the dissolution process is not only endothermic but also entropy-driving.